Effects of dietary counselling on micronutrient intakes in pregnant women in Finland. Issue 4 (19th June 2021) - Kinnunen, Tarja; Liu, Yangbo; Koivisto, Anna‐Maija; Virtanen, Suvi; Luoto, Riitta
Abstract: The intake of some micronutrients is still a public health challenge for pregnant women in Finland. This study examined the effects of dietary counselling on micronutrient intakes among pregnant women at increased risk of gestational diabetes mellitus in Finland. This study utilised data from was a cluster‐randomised controlled trial ( n  = 399), which aimed to prevent gestational diabetes. In the intervention group, the dietary counselling was carried out at four routine visits to maternity care and focused on dietary fat, fibre and saccharose intake. A validated 181‐item food frequency questionnaire was used for evaluating the participants' food consumption and nutrient intakes. The differences in changes in micronutrient intakes from baseline (pre‐pregnancy) to 36–37 weeks' gestation were compared between the intervention and the usual care groups using multilevel mixed‐effects linear regression models, adjusted for confounders. Based on the multiple‐adjusted model, the counselling increased the intake of niacin equivalent (coefficient 0.50, 95% confidence interval [CI] 0.03–0.97), vitamin D (0.24, CI 0.05–0.43), vitamin E (0.46, CI 0.26–0.66) and magnesium (5.05, CI 0.39–9.70) and maintained the intake of folate (6.50, CI 1.44–11.56), from early pregnancy to 36 to 37 weeks' gestation. Except for folate and vitamin D, the mean intake of the micronutrients from food was adequate in both groups at baseline and the follow‐up. In conclusion, the dietary counselling improved the intake of several vitamins and minerals from food during pregnancy. Supplementation on folate and vitamin D is still needed during pregnancy.